Analisis Profesionalisme Guru Sekolah Dasar Dalam Melaksanakan Pembelajaran Daring Pada Masa Pandemi Covid-19 - Dila Annisa Maharani; Iis Nurasiah; Arsyi Rizqia Amalia (Jurnal Gentala Pendidikan Dasar, 2021)
This study aims to analyze the professionalism of elementary school teachers in implementing learning during the Covid-19 pandemic. This research was conducted at SDN Kebonjati, Sukabumi City which developed from July to September. This research uses descriptive qualitative research. The subjects used in this study were one teacher for class IV A at SDN Kebonjati and students for class IV A who opened 26 people. The data collection techniques used in this research were closed questionnaires, semi-structured interviews, and documentation. Pedagogic competence as a professional teacher consists of three indicators, namely the ability to plan the learning process, the ability to manage the learning process and the ability to evaluate (assess) learning. The results showed that the teacher's ability to plan learning and the ability of teachers to evaluate learning had been done professionally, but the teacher's ability to manage learning could not be done professionally. This is due to the constraints and limitations of teachers in carrying out the courageous learning process.